Comparative in vitro and in vivo Evaluation of Different Iron Oxide-Based Contrast Agents to Promote Clinical Translation in Compliance with Patient Safety - Unterweger, Harald; Janko, Christina; Folk, Tamara; Cicha, Iwona; Kovacs, Noemi; Gyebnar, Gyula; Horvath, Ildiko; Mathe, Domokos; Zheng, Kang H.; Coolen, Bram F.; Stroes, Erik; Szebeni, Janos; et al. (International Journal of Nanomedicine, 2023)
Introduction: One of the major challenges in the clinical translation of nanoparticles is the development of formulations combining favorable efficacy and optimal safety. In the past, iron oxide nanoparticles have been introduced as an alternative for gadolinium-containing contrast agents; however, candidates available at the time were not free from adverse effects. Methods: Following the development of a potent iron oxide-based contrast agent SPIONDex, we now performed a systematic comparison of this formulation with the conventional contrast agent ferucarbotran and with ferumoxytol, taking into consideration their physicochemical characteristics, bio-and hemocompatibility in vitro and in vivo, as well as their liver imaging properties in rats. Results: The results demonstrated superior in vitro cyto-, hemo-and immunocompatibility of SPIONDex in comparison to the other two formulations. Intravenous administration of ferucarbotran or ferumoxytol induced strong complement activation-related pseu-doallergy in pigs. In contrast, SPIONDex did not elicit any hypersensitivity reactions in the experimental animals. In a rat model, comparable liver imaging properties, but a faster clearance was demonstrated for SPIONDex. Conclusion: The results indicate that SPIONDex possess an exceptional safety compared to the other two formulations, making them a promising candidate for further clinical translation.
CRIS-Team Scopus Importer:2023-05-26
Keywords: CARPA; complement activation; magnetic resonance imaging; MRI; nanomedicine; nanoparticles